PRESUMPTION OF INNOCENCE OF LEGAL PERSONS - Golts, Edgars (Administrative and Criminal Justice, 2016)
There is a link between a presumption of innocence and the right to a fair trial. The rights of a legal person, to be regarded as innocent, protection is ensured by the guarantees in law. The Court of Justice has recognized that the right to the presumption of innocence, the legal persons does not apply in the same way as natural persons. The Constitution reinforces the presumption of innocence is to be subject to the right to a fair trial arising from the principle of justice. The Constitution stipulates that the rights of the person may be limited to the benefit of the public, but not the right to the presumption of innocence. In the article the author expresses the conviction, nowadays, the development of such rights, – the environment, animal, unborn children, deceased persons and other types of law; it is obvious that, on the basis of an equity principle, human rights are extended translated and applied. Justice fully embraces the principles of equality law, which allows concluding on the physical and legal persons to equality before the law and the courts.